Occlusal‐based planning for dental rehabilitation following segmental resection of the mandible and maxilla. Issue 3 (27th November 2020) - Leinkram, David; Wykes, James; Palme, Carsten; Deshpande, Suhas; McLaughlin, Matthew; Garg, Pooja; Wallace, Christine; Howes, Dale; Clark, Jonathan R.
Abstract : Reconstruction of the maxilla and mandible incorporating a dental prosthesis supported by dental implants is a complex process but has tremendous benefit to patient rehabilitation following ablative procedures. This study presents a protocol that can be used to aid other institutions to provide the highest standard of reconstruction.